Praktik Alih Kode dan Campur Kode di Komunitas Ngaji Nahwu: Analisis Sosiolinguistik - Urwati, Nursyahidatul; Alamsyah, Firman; Munip, Abdul (STIQ Amuntai, 2025)
This study investigates the phenomenon of code-switching and code-mixing within the Ngaji Nahwu learning community by focusing on their forms, functions, and epistemological implications. Using a qualitative descriptive approach, data were collected through participant observation, audio recordings, and semi-structured interviews, and analyzed with the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings reveal that code-switching and code-mixing occur in functional, technical, and educational contexts. Arabic is predominantly used to convey grammatical terms and illustrative examples, while Indonesian—and occasionally English—is employed to clarify and reinforce meaning. Code-mixing frequently takes the form of Arabic words and phrases embedded within Indonesian sentence structures, whereas code-switching appears when speakers shift entirely from one language to another to improve teaching effectiveness. These linguistic practices are a distinctive feature of kitab kuning-based learning communities, as they naturally integrate classical scholarly traditions with modern communicative approaches, thereby offering valuable insights into bilingual strategies that enhance comprehension and pedagogical effectiveness in contemporary Islamic education.